The African American Sermon as an Exemplar of Culturally Relevant Adult Education - E. Paulette Issac; Michael L. Rowland (Adult Education Research Conference, 2002)
Historically, through different avenues, the Black Church has been culturally responsive to the needs of African American learners. One such avenue has been the African American sermon. The purpose of this study was to conduct a contextual analysis of African American sermons to identify culturally relevant themes and their applicability for use in adult education classrooms.